2013
DOI: 10.1080/01576895.2013.769861
|View full text |Cite
|
Sign up to set email alerts
|

The zine anthology as archive: archival genres and practices

Abstract: Sydney (UTS) and a casual academic in the Information Studies programs at both UTS and Charles Sturt University. Her doctoral research focuses on the archival practices of subcultural communities and how this furthers temporal and spatial understandings of archives. Building on Eichhorn's concept of 'archival genres', this article considers the recent spate of zine anthologies published in Australia and the United States as examples of these genres. It proposes that the anthologies are archives of content, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A related discussion that the present study contributes to concerns the applicability of the metaphor of the archive to accentuate the preservational capacity of the Internet (see Bowker, 2005;Lymn, 2013). This extension of the concept of archive has been criticized by, among others, Ernst (2013) and Chun (2008), who find that the notion becomes generalized to the point where it loses meaningfulness.…”
Section: Discussionmentioning
confidence: 86%
“…A related discussion that the present study contributes to concerns the applicability of the metaphor of the archive to accentuate the preservational capacity of the Internet (see Bowker, 2005;Lymn, 2013). This extension of the concept of archive has been criticized by, among others, Ernst (2013) and Chun (2008), who find that the notion becomes generalized to the point where it loses meaningfulness.…”
Section: Discussionmentioning
confidence: 86%
“…And the audience itself can be a crucial access point. Lymn (2013) found that "how people acquire zines is often just as interesting and engaging as what is in the zine itself. The acquisition highlights the materiality not just of the object but of the engagement" (p. 46).…”
Section: Cataloging Norms and Matters Of Descriptionmentioning
confidence: 97%
“…The documentary voice in zines is personal and participatory, lending a more holistic explanation of issues than a bystander's news report (Atton, 2001;Dodge, 1995). Because zines exist outside of the mainstream, they provide testimony of sub-and countercultures (Ardito, 1999;Lymn, 2013;Wooten, 2012) as well as progressive political attitudes and thought (Congdon & Blandy, 2005;Kucsma, 2002). Zines inscribe marginalized perspectives, sometimes controversial ones (Congdon & Blandy, 2005;Duncombe, 1997;Gisonny & Freedman, 2006;Gomez, 2007;Koh, 2008;Kucsma, 2002;Morgan & Dawson, 2010;Sellie, 2006).…”
Section: Users and Research Needsmentioning
confidence: 98%
“…Other authors explore zines as alternative or underground literature and culture (Dodge 2008;Herrada and Aul 1995;Koh 2008), or provide other practical coverage like how to catalog them (Berman 2005;Carlton 2015; Freedman and Kauffman 2013; O'Dell 2014), digitization efforts (Chant 2015), resources (Brett 2010), and programming (Gómez 2007). Librarians being librarians, the literature also includes reviews, bibliographies, and literary criticism (Barack 2006;Finnell 2013;Lymn 2013;Sellie 2006).…”
Section: Zines In Lis Literaturementioning
confidence: 99%